TREE COMMUNITY STRUCTURE AND ABOVEGROUND CARBON STOCK OF SACRED FOREST IN PASAMAN, WEST SUMATERA - Santhyami Santhyami (SEAMEO BIOTROP, 2021)
This is an analysis of the tree community’s composition and structure of Bukit Badindiang sacred forest in Nagari Simpang, Pasaman West Sumatera. The study aims to (1) to obtain a representative account of the structure and composition of tree community of the sacred forest, (2) to estimate the Aboveground Carbon Stock (C-Stock) accumulated on it. A one-hectare plot was divided into 25 subplots of 20 m × 20 m each for tree and debris data collection. In each subplots, there would be a 5m x 5m sapling subplots and 1m x 1m seedling, understorey plant and litter subplots were nested inside. A total of 446 trees were recorded, representing 139 species from 49 families with a total basal area of 38.59 m2. The most dominant tree species was Campnosperma auriculata [Importance Value (IV) of 19.19]. The other prevalent species were Ficus benjamina (IV =16.50) and Mallotus caudatus (IV =14.78). A total of 62 species (44.6%) was considered locally rare with density of 1 tree/ha. Mallotus caudatus had the highest density (37 trees/ha) and Ficus benjamina had the highest Basal Area (BA) (5.61 m2 = 14.51% of the total). Euphorbiaceae (IV= 37.40) was the dominant family. The richest families were Euphorbiaceae (10) and Lauraceae (10). The total estimated Aboveground C-Stock was 190.62 MgC/ha, with the highest C was contributed by trees (178.85 MgC/ha or 93.8% of total). Trees with diameter class of 10 – 69.99 cm stored 62% of total tree carbon. The species richness, tree density and C-Stock of Bakit Badindiang sacred forest were relatively higher than those in several disturbed lowland forests in Sumatera.